(3GdHfhc GdESdGejI (B:s (3GdJLQHI Hjf Gdabg hGdbGfhf hGdJWHjb (B/s - (3GdeGdbj, YGFTI GdTQbGhjs ((3GdOGQ GdHjVGA(B: s (3GdeQcR GdKbGaj GdYQHj(B, s, 2002)
(3GdhVYjI GdbGfhfjI dJCSjS hEOGQI GdHfhc GdESdGejI , EOGQI GdHfhc GdESdGejI hGdQbGHI YdjgG , ehGQO GdHfhc GdESdGejI , COhGJ JhXja GdCehGd aj GdHfhc GdESdGejI , GdJhXja HGdeVGQHI Ch Jehjd GdYed , GdJhXja HfGA Ydi eHOC GdgGeT GdQHMj , GdJhXja HOhf gGeT QHMjs
(3GdeQGLY U(B.691s
Keywords: (3GdEFJeGfs; (3GdESdGe hGdHfhcs; (3GdEbJUGO GdESdGejs